3-D seismic images of an extensive igneous sill in the lower crust - Wrona,T; Magee,C; Fossen,H; Gawthorpe,RL; Bell,RE; Jackson,C; Faleide,JI (Geology, 2019)
When continents rift, magmatism can produce large volumes of melt that migrate upwards from deep below the Earths surface. To understand how magmatism impacts rifting, it is critical to understand how much melt is generated and how it transits the crust. Estimating melt volumes and pathways is difficult, however, particularly in the lower crust where the resolution of geophysical techniques is limited. New broadband seismic reflection data allow us to image the three-dimensional (3-D) geometry of magma crystallized in the lower crust (17.5-22 km depth) of the northern North Sea, in an area previously considered a magma-poor rift. The sub-horizontal igneous sill is 97 km long (N-S), 62 km wide (E-W), and 180 40 m thick. We estimate that 472 161 km3of magma was emplaced within this intrusion, suggesting that the northern North Sea contains more igneous intrusions than previously thought. The signi cant areal extent of the intrusion ( 2700 km2), as well as presence of intrusive steps, indicate sills can facilitate widespread lateral magma transport in the lower crust.